Benefits and risks of antihypertensive medication in adults with different systolic blood pressure: A meta-analysis from the perspective of the number needed to treat - Mao, Yucheng; Ge, Shiyao; Qi, Sufen; Tian, Qing-Bao (Frontiers in Cardiovascular Medicine, 2022)
Background: The blood pressure (BP) threshold for initial pharmacological treatment remains controversial. The number-needed-to-treat (NNT) is a significant indicator. This study aimed to explore the benefits and risks of antihypertensive medications in participants with different systolic BPs (SBP), and cardiovascular disease status from the perspective of the NNT. Methods: We conducted a meta-analysis of 54 randomized placebo-controlled trials. The data were extracted from published articles and pooled to calculate NNTs. The participants were divided into five groups, based on the mean SBP at entry (120-129.9, 130-139.9, 140-159.9, 160-179.9, and ≥180 mmHg). Furthermore, we stratified patients into those with and without cardiovascular disease. The primary outcomes were the major adverse cardiovascular events (MACEs), and adverse events (AEs) leading to discontinuation. Results: Antihypertensive medications were not associated with MACEs, however, it increased AEs, when the SBP was <140 mmHg. For participants with cardiovascular disease or at a high risk of heart failure and stroke, antihypertensive treatment reduced MACEs when SBP was ≥130 mmHg. Despite this, only 2-4 subjects had reduced MACEs per 100 patients receiving antihypertensive medications for 3.50 years. The number of individuals who needed to treat to avoid MACEs declined with an increased cardiovascular risk. Conclusions: Pharmacological treatment could be activated when SBP reaches 140 mmHg. For people with cardiovascular disease or at a higher risk of stroke and heart failure, 130 mmHg may be a better therapeutic threshold. It could be more cost-effective to prioritize antihypertensive medications for people with a high risk of developing cardiovascular disease.